Assessing hydrological effects and performance of low impact development practices based on future scenarios modeling. (1st April 2018) - Wang, Mo; Zhang, Dong Qing; Su, Jin; Dong, Jian Wen; Tan, Soon Keat
Abstract: Future scenarios modeling has been conducted to investigate the effectiveness of urban stormwater infrastructure and to cater to potential future changes. The changes of quantity and quality of urban stormwater, and attributable to climate change and urbanization, were examined and tested in four urban catchments based on future scenarios modeling. Based on our findings, we observed that there were different degrees of performance corresponding to 2-, 10-, and 100-year design storms. However, the general patterns and insights deduced were similar: (1) the peak runoff and water quality appeared to be impacted more significantly by urbanization factors than that due to climate change; (2) the influence from urbanization (increase intensity of land use and population density) was found to be more significant than that from land-use changes alone; (3) catchments with relatively rapid developing rates appeared to produce more serious adverse influence on the stormwater quabntity and quality; and (4) low impact developments as key adaptation practices could be potentially effective in mitigating adverse impacts of future changes on urban stormwater system. The methodology developed in this study could be useful for urban stormwater planning and testing the plan against future change scenarios as a result of urbanization and climate change. Graphical abstract: Highlights: Hydrologic response may be impacted more significantly by urbanization. Future changes may have more effects on the quality of runoff than on quantity. Rapidly developing catchments may produce more adverse influence on urban hydrology. Stormwater in downtown area will be harder to manage than that in developing areas. LID could be effective in mitigating impacts on stormwater from future changes.